THE INFLUENCE OF D-I-A LEARNING METHODS (DELEVERY, INTERACTION, ASSESSMENT) AND LEARNING MOTIVATION ON SEPAKTAKRAW LEARNING OUTCOMES - jufrianis jufrianis; Dedi Ahmadi; Muhammad Syahrul Rizal; Kasman Ediputra (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2023)
This research aims to determine the effect of the D-I-A learning method (Delevery, Interaktion and Assessment) on sepaktakraw learning outcomes. The research sample consisted of 64 people who were students of physical education, health and recreation at Pahlawan University using a 2 x 2 treatment by level research design. The data were analyzed using analysis of variance (ANOVA) and continued with the Tukey test at a significance level of Î± = 0.05. The results of the research show (1) in general, there are differences between the D-I-A Learning Method (Delevery, Interation, Assessment) on sepaktakraw learning outcomes (FO7,55>4,00 Ft), (2) there is an interaction between the D-I-A learning method (Delevery, Interaktion and Assessment) on sepaktakraw learning outcomes (FO14,53>4,00 Ft), (3) in students with high motivation towards learning sepaktakraw (4) there is a significant influence on the results of learning sepaktakraw with the D-I-A (Delevery, Interation, Assessment) method of (QO2,16< 5,13 Qt). The conclusion of this research is that there is a significant influence of the D-I-A learning method (Delevery, Interation, Assessment) and Motivation on the sepaktakraw learning outcomes of Physical Education Health and Recreation students at Pahlawan Tuanku Tambusai University.